Spiritual Quotient (SQ) Of The Prophet Muhammad SAW. Perspectives Of Hadith and Sirah Nabawi - Fadhlina Arief Wangsa; I Gusti Bagus Agung Perdana Rayyn (Al-Ulum, 2025)
This research deals with spiritual quotient based on the perspective of the Prophet Muhammad's hadith and Prophetic narrative (Sirah Nabawi). The research was conducted using hadith science and psychology as research approaches. This research is a scientific literature-based research that is descriptive qualitative and is a library research. The results found in this study that basically quotient is not only intellectual quotient and emotional quotient, but there is also what is called spiritual quotient. In Islam, the spiritual quotient has been taught by the Prophet Muhammad PBUH in life as well as in his various traditions which can be seen in the Sirah nabawi. The spiritual quotient taught by the Prophet Muhammad in his hadith and life (Sirah nabawi) is the main indicator of piety. Piety can be achieved by being generous, and getting closer to Allah swt. by interacting with Him through worship and remembrance (dhikr).